2016
DOI: 10.2147/dmso.s113874
|View full text |Cite
|
Sign up to set email alerts
|

Coaching and barriers to weight loss: an integrative review

Abstract: IntroductionCoaching is proposed to raise a patient’s awareness and responsibility for their health behaviour change by transforming the professional–patient relationship.ObjectiveTo review the scientific literature on how coaching can assist in weight loss and improve a patient’s state of health.MethodologyAn integrative literature search was performed using PubMed, Latin American and Caribbean Literature in Health Sciences, and Scientific Electronic Library Online. We selected articles that were published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…It should be noted that several new and important HWC reviews were published in the previous 2 years. 6,16,35,36 These summarized HWC research on cancer, 6 obesity, 36 and diabetes, 16 with each concluding a beneficial effect of HWC. Dejonghe et al 35 reviewed HWC long-term effectiveness and revealed coaching may have an impact more than 6 months after stopping treatment, though these authors clearly called for more research before reaching firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that several new and important HWC reviews were published in the previous 2 years. 6,16,35,36 These summarized HWC research on cancer, 6 obesity, 36 and diabetes, 16 with each concluding a beneficial effect of HWC. Dejonghe et al 35 reviewed HWC long-term effectiveness and revealed coaching may have an impact more than 6 months after stopping treatment, though these authors clearly called for more research before reaching firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention MyPyramidPlanner had a research assistant to travel to the women’s homes up to three times a week to assist with childcare, facilitate the exercises, and have a weekly face-to-face talk about dietary intake [31]. Accordingly, the ICT-part of the interventions can be seen as a supplement to personal counseling, and personalized counseling is important for achieving weight loss goals [36]. However, the Nintendo Wii also showed a significant change in weight loss, so ICT interventions without counseling may be successful by using gaming.…”
Section: Discussionmentioning
confidence: 99%
“…Learning self-management and self-help within a framework of a lifestyle or a chronic diseases management program supports clients and patients in health literacy, self-competence, and participation. 38 , 39 However, this approach is a big challenge for client, patient, and coaches involved equally in this process.…”
Section: Discussionmentioning
confidence: 99%